Replacement control of Mikania micrantha in orchards and its eco-physiological mechanism - Jia, Pu; Wang, Jiayi; Liang, Haolin; Wu, Zhuo-hui; Li, Fenglin; Li, Weihua (Frontiers in Ecology and Evolution, 2022)
Mikania micrantha is one of the most notorious invasive weeds in south China, especially in orchard habitats. Based on the principle of niche competition, screening plants with strong competitiveness and managing vacant niches through natural alternative methods (replacement control) were expected to achieve sustainable ecological management of invasive species. To this end, two legumes, Desmodium heterocarpon and Senna tora, were selected to conduct field competition experiments with M. micrantha to investigate the interspecific competitiveness of these two legumes and M. micrantha from the aspects of adaptability to low light and response to drought stress. We found that the relative interaction indexes of D. heterocarpon and S. tora to M. micrantha were both negative and the competitive inhibition of S. tora on M. micrantha was higher than that of D. heterocarpon. Compared with M. micrantha, D. heterocarpon and S. tora have higher photosynthetic efficiency and lower dark respiration efficiency under low-light conditions, thus maintaining positive plant carbon balance capacity in the low-light understory and becoming more shade-tolerant. Besides, the water stress experiment found that M. micrantha had the lowest tolerance to drought stress, followed by S. tora, and D. heterocarpon was the most drought tolerant. These results showed that D. heterocarpon and S. tora can effectively prevent and control M. micrantha, mainly due to their higher competitiveness, shade tolerance, and drought tolerance. The control effect of D. heterocarpon is better than that of S. tora which is an alien species. Therefore, we believed that the replacement control of the invasive weed M. micrantha by D. heterocarpon is expected to be a sustainable ecological management strategy for M. micrantha biocontrol in the dryland orchard habitat. These findings provide a theoretical basis for the selection of species for alternative control in the future and provide new ideas for solving the problem of repeated regeneration in the existing M. micrantha control process.